[NEW TWIST IN THE BIZARRE TALE OF THE HHS EXECUTIVE ORDER] - STUNTZ S (Tufts Archival Research Center, 2007)
Memo regarding the controversy over the executive order from HHS ordering a smoking ban. Asks for information on where the unions stand on the revisions made. Doubts that HHS will accept the revisions as they wouldn't satisfy their goal.